Modeling of a two-phase flow of liquid with small-size gas bubbles - Vasenin, I.M.; Narimanov, R.K.; Shrager, L.A.; Perchatkina, E.V. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
The model of the motion of a gas-liquid medium with small-size bubbles in a gravity field following free and forced convection was proposed. The model automatically takes into account the processes causing free convection in gravity field in the presence of heterogeneous concentration of bubbles. Compared to the model of interpenetration continuums to describe a two-phase medium, this model does not contain small parameters for derivatives. The two-phase flow in context of the problems similar to the water ozonation problem in contact tanks is considered. The analogy to compressible gas models allows obtaining the solution using well-established numerical solution schemes.
Keywords: two-phase flow; gas-liquid medium; small-size bubbles; heterogeneous; water ozonation